Spatiotemporal Regulation of Injectable Heterogeneous Silk Gel Scaffolds for Accelerating Guided Vertebral Repair. Issue 7 (18th January 2023) - Wang, Tianji; Liu, Keyin; Wang, Jing; Xiang, Geng; Hu, Xiaofan; Bai, Hao; Lei, Wei; Tao, Tiger H.; Feng, Yafei
Abstract: Osteoporotic vertebral fracture is jeopardizing the health of the aged population around the world, while the hypoxia microenvironment and oxidative damage of bone defect make it difficult to perform effective tissue regeneration. The balance of oxidative stress and the coupling of vessel and bone ingrowth are critical for bone regeneration. In this study, an injectable heterogeneous silk gel scaffold which can spatiotemporally and sustainedly release bone mesenchymal stem cell‐derived small extracellular vesicles, HIF‐1 α pathway activator, and inhibitor is developed for bone repair and vertebral reinforcement. The initial enhancement of HIF‐1 α upregulates the expression of VEGF to promote angiogenesis, and the balance of reactive oxygen species level is regulated to effectively eliminate oxidative damage and abnormal microenvironment. The subsequent inhibition of HIF‐1 α avoids the overexpression of VEGF and vascular overgrowth. Meanwhile, complex macroporous structures and suitable mechanical support can be obtained within the silk gel scaffolds, which will promote in situ bone regeneration. These findings provide a new clinical translation strategy for osteoporotic vertebral augmentation on basis of hypoxia microenvironment improvement. Abstract : An injectable heterogeneous silk gel scaffold with spatiotemporal dual sustained drug release reinforces osteoporotic vertebral body and promotes angiogenesis as well as bone regeneration. The study provides an insight into the issues of the current material in clinical practice and represents an innovative biomaterial based on silk to achieve vertebral augmentation.